Linking research and policy: The case of Ghana's rice trade policy - deGrassi, Aaron (International Food Policy Research Institute, 2007)
Agricultural trade policies, in particular import tariffs to protect domestic production, constitute a highly contested field of agricultural policy. In view of the recent focus on “evidence-based policy making” in the international development debate, the question arises as to which extent research-based evidence is used in such policy decisions, and which role research plays as compared to other political factors. Against this background, this paper seeks to examine and explain research-policy linkages in the case of rice tariff reform in Ghana. It is based on literature reviews and 70 interviews. The paper uses a historical cultural political economy approach, and reveals that in order to understand the actions of Ghana’s policy makers, there is a need to go beyond currently used approaches to understanding politics in order to reveal the complex factors that underlie such policy decisions. The paper starts by locating the study in the framework of the recent interest of the international development community in agriculture on the one hand, and in evidence-based policy-making on the other. The paper then reviews the recent literature on then links between research and policy making. After briefly describing the study’s conceptual framework and methodology, the paper gives an overview of Ghana’s governance, political dynamics, socio-economic trends, agricultural policies, which provide the setting for research-policy linkages. The presentation of the findings of the study starts with a general description of the links between research and policy that have been observed in agricultural policy-making in Ghana. In order to discover the underlying factors in linking research and policy requires examining particular conceptual lenses (“discourses”) in Ghana, as well the intricate politics of elections, nationalism, external pressure, and rifts with civic campaigners. To see whether or not the nature of linkages is unique to the rice sector, the report also contrasts the case of rice with on the case of agricultural mechanization.